Stochastic modelling of burden of livestock diseases on domestic ruminants in Ethiopia - Jemberu, Wudu T.; Chaters, G.; Knight-Jones, Theodore J.D.; Gilbert, W.; Kwok, S.; Bruce, M.; Huntington, B.; Rushton, J. (Elsevier, 2026)
This study, carried out in 2022-2023, quantified the financial burden of disease in cattle, sheep and goats in Ethiopia for the year 2021 using the animal health loss envelope (AHLE) metric. The AHLE measures all cause disease burden, avoidable and non-avoidable, as the difference in the financial performance of a livestock production system (e.g., gross margin) comparing a scenario where animals are in an ideal state of health to the current situation. A stochastic dynamic population model (DPM) was employed to calculate the gross margin for an average farm and for the national herd under these current and ideal health scenarios. Data for parametrizing the DPM were derived from secondary sources and expert elicitation. The stochastic DPM was simulated for10,000 iterations and results are reported as means with 95% percentile intervals (PI). The annual AHLE per average farm was estimated at USD 1,209 (95%PI:392-2,470) in cattle, USD 158 (95%PI:66-292) in sheep and USD 416 (95%PI:136-847) in goats. At national level, the annual AHLE in ruminants was USD 18.39 billion with USD 15.42 billion (95% PI:12.70-18.57) in cattle, USD 1.04 billion (95% PI:0.84-1.30) in sheep, and USD 1.93 billion (95% PI:1.64 - 2.25) in goats. Morbidity losses constituted the largest component of the AHLE, exceeding 50% across all species, while animal health expenditure represented the smallest component, accounting for less than 2% of AHLE in all species. This high disease burden, with minimal contribution from animal health expenditure, indicates significant opportunity for improvement through investment in animal health.